Peranan Guru Dan Siswa pada Kegiatan Perintisan Sekolah Berwawasan Lingkungan dan Mitigasi Bencana Alam (SWALIBA) (Faculty of Social Science, Universitas Negeri Semarang, 2016)
This study aims to determine the role of teachers and students in the Swaliba pilot program, and determine the supporting factors and inhibiting Swaliba pilot program. Research conducted at SMPN 41 Semarang, the research subjects are teachers and students of SMPN 41 Semarang. used in this study. Data were collected through interviews, observation, documentation and questionnaires, and analyzed using descriptive percentages. The results were obtained: (1) The teachers role in the environmentare at high criteria, in the disaster are at moderatecriteria; the students role in the environmentfield are at high criteria , while for the disaster fieldare in the low criteria. (2) Swaliba pilot program in SMP N 41 Semarang can be run for their supporting factors, like the active participation of all citizens of the school, the availability of facilities and infrastructure, a good cooperation with schools partner even if constrained by the curriculum implementation, monitoring and schools partner cooperation.